STUDI KOMPARATIF PEMBERIAN KOMPRES HANGAT DAN TEPIDSPONGE TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DENGAN KEJANG DEMAM DI RSUD dr. SOEDARSONO PASURUAN - Rizky Nur Laili (Poltekkes Kemenkes Malang, 2018)
The high body temperature becomes the trigger factor of febrile seizures. A febrile seizure is a medical solubility that requires immediate relief. Handling of nurses at the time of seizure in progress is to provide anti-seizure and anti-pyretic drugs according to the doctor's instructions then non-pharmacological nursing actions. The purpose of this study was to find out the compressive compresses of temporal and tepidsponge to the decrease of body temperature in children with febrile seizures in RSUD dr. Soedarsono Pasuruan. Design used is Quasy Experimental with Pre-Test and post-Test Design With Comparison Treatment. Population in this study are all patients who experienced febrile seizures in dr. Soedarsono Pasuruan. Samples divided into 2 groups, warm compress group and tepidsponge group, each of 15 people, taken by purposive sampling technique. Analysis used univariate and bivariate with Paired T Test and Independent T Test. The statistical test results show that there is a difference in the temperature drop between warm compresses with p value = 0,000. Suggestions for Hospitals, the results of this study can be used as input for standard operational procedures in lowering the body temperature of children with febrile seizures non-pharmacologicallywithtepidsponge.